2013
DOI: 10.1007/jhep10(2013)132
|View full text |Cite
|
Sign up to set email alerts
|

Cornering light neutralino dark matter at the LHC

Abstract: We investigate the current status of the light neutralino dark matter scenario within the minimal supersymmetric standard model (MSSM) taking into account latest results from the LHC. A discussion of the relevant constraints, in particular from the dark matter relic abundance, leads us to a manageable simplified model defined by a subset of MSSM parameters. Within this simplified model we reinterpret a recent search for electroweak supersymmetric particle production based on a signature including multi-taus pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 139 publications
2
48
0
Order By: Relevance
“…[95] for this model. Some general studies regarding light neutralinos can be found in [107][108][109][110][111][112][113][114][115][116]. On the other hand, in the regime of small Yukawa coupling f ∼ 10 −4 , the Higgs boson mass is devoid of any large tree level contribution.…”
Section: Jhep02(2015)124mentioning
confidence: 99%
See 1 more Smart Citation
“…[95] for this model. Some general studies regarding light neutralinos can be found in [107][108][109][110][111][112][113][114][115][116]. On the other hand, in the regime of small Yukawa coupling f ∼ 10 −4 , the Higgs boson mass is devoid of any large tree level contribution.…”
Section: Jhep02(2015)124mentioning
confidence: 99%
“…In this case, this is the lightest supersymmetric particle (LSP) and its mass is mainly controlled by the R-breaking Majorana gaugino mass parameter M 1 . A very light neutralino has profound consequences in both cosmology as well as in collider physics [107][108][109][110][111][112][113][114][115][116]. In the context of the present model one can easily satisfy the stringent constraint coming from the invisible decay width of the Z boson because the light neutralino is predominantly a bino.…”
Section: Jhep02(2015)124mentioning
confidence: 99%
“…Here we emphasize that our conclusions are based on a common slepton mass assumption, and if onlyτ s are assumed to be light, the conclusions may change slightly. Indeed, for the latter case a study similar to what we did must be done, and the experiment pertinent to theτ search should be considered [34]. We also want to emphasize that the cuts in our simulation at the 14 TeV LHC can be optimized, and meanwhile the pileup effect should be estimated.…”
Section: Jhep03(2016)207mentioning
confidence: 99%
“…Recent discussions on the light DM scenario concentrated on the complement of new experimental constraints, such as those from the 125 GeV Higgs data and the direct searches for sparticles at the LHC, and consequently the allowed parameter space of the scenario shrinks significantly [34][35][36][37][38][39][40][41]43]. For example, it was found that the lower bound of mχ0 1 could be improved from about 10 GeV to roughly 25 GeV after considering the searches for multi-τ plus large E miss T signal at the early stage of the LHC Run-I [34].…”
Section: Jhep03(2016)207mentioning
confidence: 99%
See 1 more Smart Citation